Effect of Smoking History on Inpatient Postpartum Opioid Use [2K] - Blitz, Matthew J.; Prasannan, Lakha; Greenberg, Meir; Marchbein, Harvey; Rochelson, Burton L. (Obstetrics and gynecology (New York. 1953), 2019)
INTRODUCTION:To determine if inpatient postpartum opioid utilization is affected by smoking history. METHODS:Retrospective cohort of singleton deliveries at ≥37 weeks of gestation in which smoking status was documented on admission at a tertiary hospital from 2013-2016. Patients were excluded for NSAID or opioid allergies, drug abuse history, positive urine toxicology, general anesthesia for delivery, and incomplete records. Outcomes evaluated were mode of delivery, medications administered for postpartum analgesia, and total doses received. RESULTS:A total of 17,280 pregnancies were included83 current, 890 former and 16,307 non-smokers. The cesarean delivery rate was higher among current or former smokers compared to non-smokers (45.9% vs. 34.3%, P<0.0001). After cesarean delivery, current or former smokers were more likely to receive oxycodone (82.3% vs. 75.8%, P<0.002), to have it administered at higher total amounts (98 vs. 84 grams, P<0.001), and to exceed the 90th percentile for consumption (12.5% vs. 8.3%, P<0.009). After vaginal delivery, current or former smokers were also more likely to receive oxycodone (41.8% vs. 31.3%, P<0.0001), to have it administered at higher total amounts (54 vs. 42 grams, P<0.0001), and to exceed the 90th percentile for consumption (15.9% vs. 9.2%, P<0.003). There was no difference in the rate of additional breakthrough opioid medications based on smoking history. CONCLUSION:Women who are current or former smokers are more likely to receive oxycodone for postpartum analgesia compared to non-smokers, and at increased amounts. A precision medicine approach using personalized treatment algorithms may improve pain management in this population.